A survey of life-long reading habits among UiTM undergraduates / Soo Kum Yoke, Evelyn Sharmannie and Ahmad Azman - Soo, Kum Yoke; Sharmannie, Evelyn; Azman, Ahmad (Institute of Research, Development and Commercialization (IRDC), 2007)
This study intents to look at the English Language reading habits of Universiti Technologi MARA Johor undergraduates for the purpose of finding out the reading culture among the undergraduates and the strategies to enhance life-long reading habits. It will thus look at the internal and external factors such as self-motivation, availability of reading materials, role of peers, role of motivators (i.e. family, teachers, government, media) and competition from modern devices (i.e. computer, video games, television etc) that challenges the acquisition of life-long reading habits.